ANALISIS MODEL EVALUASI DAN PENJAMINAN KUALITAS PENDIDIKAN BERBASIS TEKNOLOGI - Ilham Jaya Abd Rauf; Ike Krismawati; Hanief Abdillah Arif; Andi Warisno; Nila Wati Tajuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has transformed the education sector, creating new opportunities and challenges in maintaining educational quality. Technology-based education requires a systematic evaluation and quality assurance model to ensure the effectiveness, efficiency, and sustainability of the learning process. This study aims to analyze evaluation models and quality assurance systems in technology-based education, focusing on planning, implementation, monitoring, and continuous improvement processes. The study employs a literature review approach by examining various theories, research findings, and policies related to digital education quality assurance. The findings indicate that effective evaluation models should integrate technological, pedagogical, and managerial aspects to measure learning outcomes, user satisfaction, system performance, and institutional readiness. Furthermore, quality assurance plays a strategic role in maintaining educational standards, enhancing accountability, and supporting innovation in digital learning environments. Therefore, educational institutions need to develop comprehensive evaluation frameworks and sustainable quality assurance mechanisms to improve the quality and competitiveness of technology-based education in the digital era.